Analytic solutions of some partial differential equations by using homotopy perturbation method - Ugurlu, Yavuz; Inan, Ibrahim E.; Kilic, Bülent (My University, 2011)
In this paper, we use the homotopy perturbation method (HPM) in order to find the analytic solutions of Clannish random walkers equation, three-dimensional nonlinear parabolic partial differential equation, molecular recombination problem and a in homogeneous coupled Burger's equation. The method does not need linearization or weak nonlinearity assumptions. In this scheme, solution is calculated in the form of a convergent power series with easily computable components. © IDOSI Publications, 2011.
Keywords: Clannish random walkers equation; Homotopy perturbation method (HPM); Inhomogeneous coupled burger's equation; Molecular recombination problem; Three-dimensional linear parabolic equation